Nauczyciel i uczeń w językowych relacjach grzeczności. Polskie formy adresatywne na Ukrainie - Krawczuk, Ałła (Słowo. Studia językoznawcze, 2012)
The article is devoted to the analysis of the established forms of address used by pupils and students addressing teachers (school and academic) and vice versa in the Polish speaking environment in Ukraine. The material is based on overheard authentic communication situations, different types of questionnaires, spoken and written utterances of pupils, teachers, students and lecturers as well as Polish language press currently published in Ukraine. The author takes into consideration Polish nationwide traditions and new tendencies in using of address forms while analyzing material. An attempt is made to determine the reasons and motivations of using peculiar school and academic forms of address, which differ from their formal Polish nationwide equivalents, in the Polish speaking environment of Ukraine.